Tingkat Kesetaraan Gender Ingkat Kesetaraan Gender Pada Industri Kulit Di Propinsi Daerah Istimewa Yogayakarta - Unggul Priyadi; Budi Astuti (Economic Journal of Emerging Markets, 2003)
Leather industry is one of small industries in Special Yogyakarta Province which contributes Regional Gross Domestic Product (PDRB) and generates employment. This re¬search analyzes cross section data in 2000th using purposive sampling method for data col¬lecting. Data analysis is Gender Inequality and Equivalent Index (IKKG) and Logit Model. Based on the empirical analysis, conclusions of this research are: 1) IKKG of entrepreneur leathers who have Educational Elementary School (SD), SMP, and SMA is 0 (zero). IKKG of the Leather Industrial person according to educational background is only female who has high education, with the value of 1, on the other hands the lower level education background has 0 (zero) value of IKKG. 2) The value of IKKG of the female workers who have SD, SMP, and SMA education background have lower chance to work compared with the male worker. Even that so the chance of SD workers is bigger than that of SMP or SMA workers. 3) The production expansion probability on leather industry is altogether affected by management’s perspectives genders, business managing experience, level of education and mounts of workers. Partially the factors affect it are: business management experience, mount of workers, and application of partnership, and on the other hand   level of education does not affect it.Key words: Gender Inequality and Equivalent Index (IKKG), Logit Model, gender perspectives.